(untitled) (Per Musi, 2018)
The composers’ search for new sound possibilities and specific timbers boosted the research and development of new percussion instruments. This article seeks to outline and discuss the definition, historical and structural aspects, diffusion and repertoire composed for Sixxen. Conceived by Iannis Xenakis, this instrument has considerably expanded its repertoire through the work of composers such as Phillipe Manoury, Michelle Agnes, among others. With regard to the historical aspects, we present points that characterized the creation of the first set of Sixxen, developed by Xenakis and Les percussions de Strasbourg. We present a review of the Sixxen sets built by various groups around the World, in addition to four companies that have developed commercial prototypes. This paper will bring an extensive documentation on an important instrumental creation of the 20th century.